SIBERIAN HUSKY DALAM KARYA SENI GRAFIS DENGAN TEKNIK LINOLEUM CUT - AYU LATIFAH, Drs. Irwan, M. Sn., Drs. Ariusmedi. M.Sn. (Universitas Negeri Padang, 2019)
Loyalty was very important in the life of human beings in various aspects, not only in the romance. As is the case with animals. Animals that do not have the intellect and the mind alone can true to its owner. One of the most famous dog breeds will be her loyalty is Siberian Husky. The Siberian Husky has a pretty fun for the man. Characteristics of the Siberian Husky can be deceived in revealing inner phenomenon with the question of the phenomenon of life. The implementation of this final work using high printing technique (Relief Print) with Linoleum. Curving techniques used for object works, and color blocks techniques used to get the form objects on the paper. The visual elements and principles of art very note in realizing the work, so that the paper looks interesting. The title of the work include: